Quantifying forest carbon dynamics as a function of tree species composition and management under projected climate - Swanteson‐Franz, Rachel J.; Krofcheck, Daniel J.; Hurteau, Matthew D. (Ecosphere (Washington, D.C), 2018)
Uncertainty remains about whether current rates of forest carbon uptake will be maintained with on‐going climate change and increasing rates of disturbance. The potential exists for climate and disturbance to exceed the physiological tolerances of certain tree species and push forest ecosystems to a point where they become C sources. Thus, a diversity of tree species with a range of physiological tolerances could provide adaptive capacity and potentially sustain a C sink despite adverse abiotic influences. The fire‐prone pine forests of the southeastern USA have been impacted by a combination of land use and fire exclusion, which has altered the demographics and composition of these historically diverse forests. We sought to quantify how prescribed fire and planting of climate‐resilient tree species would alter forest carbon dynamics under projected climate change at Fort Benning, Georgia. This landscape is comprised of a diversity of forest types with a range of land‐use histories and is heavily managed to meet military training objectives and federally listed species habitat requirements. We used a simulation approach to determine species‐specific growth responses to projected climate and develop two management scenarios: no‐management and prescribed fire coupled with planting. We ran landscape simulations of these two management scenarios under climate projections from ten global climate models to quantify how active management would alter forest carbon dynamics as a function of changing climate and wildfire. We found that the prescribed fire and plant scenario increased total ecosystem carbon ( TEC ) over our no‐management scenario by over 20 Mg C/m 2 by late century. Despite the differences in TEC , differences in net ecosystem exchange were not realized over the entire simulation. The primary drivers of TEC differences were sustained carbon uptake and lower carbon loss to wildfire in the prescribed fire and plant scenario. Our results demonstrate that under projected climate, managing to reduce the impacts of fire and planting climate‐adapted species can increase the mitigation potential of these forests.